Application of Operando X-ray Diffraction and Raman Spectroscopies in Elucidating the Behavior of Cathode in Lithium-Ion Batteries - Zhu, Wen; Liu, Dongqiang; Paolella, Andrea; Gagnon, Catherine; Gariépy, Vincent; Vijh, Ashok; Zaghib, Karim (Frontiers in Energy Research, 2018)
With the advances in characterization techniques, various operando/in-situ methods were applied in studying rechargeable batteries in order to improve the electrochemical properties of electrode materials, prolonging the battery life and developing new battery materials. In the present review, we focus on the characterization of electrode materials with operando/in-situ X-ray diffraction and Raman spectroscopies. By correlating the results obtained via these two techniques in different electrode chemistry: a) intercalation materials, such as layered metal oxides and b) conversion materials, such as elemental sulfur. We demonstrate the importance of using operando/in-situ techniques in examining the microstructural changes of the electrodes under various operating conditions, in both macro and micro-scales. These techniques also reveal the working and the degradation mechanisms of the electrodes and the possible side reactions involved. The comprehension of these mechanisms is fundamental for ameliorating the electrode materials, enhancing the battery performance and lengthening its cycling life.